Perceived Autonomy-Support Instruction and Student Outcomes in Physical Education and Leisure-Time: A Meta-Analytic Review of Correlates. [Percepción de la formación de apoyo a la autonomía y resultados en estudiantes en educación física y tiempo libre: Una revisión meta-analítica de correlaciones]. - Marc Lochbaum; Javan Jean-Noel (Ramón Cantó Alcaraz, 2016)
Physical inactivity is a global concern. Physical educators have direct access to children. Researchers have investigated the benefits of student perceived physical education (PE) autonomy-supportive instruction in PE and leisure-time (LT). Hence, a fixed-effect meta-analysis was conducted to gain an understanding of the direct effects of perceived PE autonomy-supportive instruction on a number of student outcomes. In total, 39 correlation based studies totaling 23,554 participants were analyzed with mean weighted correlation (rw) as the analyzed effect size. Nearly all effect sizes were statistically significant (p < .01). Effect sizes in PE ranged in meaningfulness from large to small across the PE categories of basic needs, emotions, motivational processes and behaviors, physical activity self-esteem, physical activity motivation, and general self-esteem/concept. For LT, effect sizes were mostly medium to small across the basics needs, motivation processes, and physical activity categories. Thus, though student perceived PE teacher autonomy-support instruction was meaningfully related to basics needs, higher level motivational processes (i.e. intrinsic motivation), and positive emotions in PE and LT, the relationships were small in meaningfulness with regards to physical activity. Future research must elucidate how perceived PE teacher autonomy-support instruction may directly improve children's physical activity to combat the global inactivity epidemic.